Analysis of Changes in Flow Setting Against Rise Time Using Gas Board 7500E Sensor on Bubble CPAP - Andjar Pudji; Farid Amrinsani; Sari Luthfiyah; Lusiana Lusiana; Shubhrojit Misra; Nur Hasanah Ahniar; Yenda Mita Barus; Lamidi Lamidi (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
Respiratory distress in neonates is one of the biggest problems encountered on a daily basis. Respiratory distress looks like rapid breathing in a newborn. CPAP Bubble is the right treatment in this case. Rise time is the time for airway pressure to reach the maximum standard value. A fast time value can make it possible to bring the breath pressure to a standard level. This study aims to analyze changes in setting flow to rise time using a gasboard sensor 7500E on a CPAP bubble device. The main advantage of this proposed method is that the results are displayed in the form of graphics, portable and there is data storage. This design uses a Gasboard 7500E sensor as a detector of oxygen concentration, a TFT LCD as a graphic display and an SD Card as data storage. The data collection is in the form of the average rise time of oxygen concentration followed by changes in its rate. Data were taken five times with three different CPAPs. The results showed that the increase in the rate affect the rise time of the CPAP oxygen concentration.